Type, Allegory, Symbol: Jonathan Edwards and Literary Traditions - Světlíková, Anna (American & British Studies Annual, 2010)
This article examines the rhetorical form of Jonathan Edwards’ (1703-1758) natural typology. Edwards, one of colonial New England’s greatest thinkers and theologians, apparently believed he was taking a bold step outside the well-established tradition of Calvinist typology, an exegetical principle based on figurative interpretation, when he argued that not only the Scripture but the created world also typologically represents divine truth. Contemporary scholars often see the natural type as a kind of proto-symbol, uniting mind and nature in a moment of transcendental perception. However, the rhetorical structure of the type suggests that Edwards’ natural type is closer to the emblematic tradition than to symbol or metonymy. While Edwards’ theory of typology might have been innovative, the literary form of the type remained traditional. The discrepancy between the content and form of Edwards’ natural typology gives us a more complex understanding of his position with respect to the allegorical and symbolist traditions.